Computer‐Aided Design of Metal Melt Filters: Geometric Modifications of Open‐Cell Foams, Effective Hydraulic Properties and Filtration Performance. Issue 2 (24th October 2021) - Lehmann, Henry; Werzner, Eric; Malik, Alexander; Abendroth, Martin; Ray, Subhashis; Jung, Bernhard
Abstract : The combination of additive manufacturing and replication technique enables the development of new ceramic foam filters (CFFs) for the filtration of metal melts based on computer‐generated templates. This article presents a numerical study on the sensitivity of filtration performance with respect to different geometric modifications, applied to an artificial monodisperse base structure. Three different geometric modifications are implemented, namely, elliptical elongation and flattening of the strut cross section with respect to the flow direction, additional finger‐like struts protruding into the pore cavity, and addition of deliberately closed windows. All modifications are implemented for overall porosities of 70–90%. The performance of the new structures is evaluated for continuous casting of aluminum by comparing the hydraulic tortuosity, the permeability, the Forchheimer coefficient, and the filtration coefficient, which are obtained from detailed pore‐scale simulations of the melt flow and inclusions transport using an Euler–Langrange approach. For the fast determination of the permeability coefficients, a novel and extremely simple model for the prediction of the Forchheimer coefficient is described. The investigation shows that geometric modifications to open‐cell foams potentially improve the filtration performance without significant decrease in filter porosity and can be considered as templates for the design of efficient CFFs. Abstract : Exploring novel designs of ceramic foam filters for metal melt filtration, the article presents a method to add 3D‐printable geometric modifications to random foams and investigates their performance in numerical simulations.